Exploring the potential of enhanced organic formulations for boosting crop productivity, nutrient utilization efficiency, and profitability in baby corn-Kabuli gram-vegetable cowpea cropping system - Garg, Kamal; Dhar, Shiva; Azman, Elisa Azura; Sharma, V. K.; Meena, Rajendra Prasad; Hashim, Mohammad; Rajawat, Mahendra Vikram Singh; Ali, Ghous; Hindoriya, Phool Singh; Kumar, Yogesh; Athnere, Sonal; Kumar, Sourabh; et al. (Frontiers Media, 2024)
The preparation of enriched formulation by integrating of agricultural wastes such as paddy husk ash (PHA) and potato peel with organic fertilizer such as farmyard manure (FYM), compost can enrich the soil with essential plant nutrients, leading to higher yields in subsequent crops and potentially reducing the dependence on farmyard manure/compost alone. However, there is lack of adequate research findings regarding the impact of different formulations generated from agricultural waste on productivity, nutrient utilization efficiency and profitability of baby corn-kabuli gram-vegetable cowpea cropping system. Therefore, a two-year field experiment (2020–2022) was conducted ICAR-IARI, New Delhi with baby corn-kabuli gram-vegetable cowpea cropping system. Seven nutrient sources were tested in Randomized Block Design and replicate thrice.The results showed that treatment T4 (100% recommended dose of nitrogen (RDN) through PHA based formulation) had significant effect on crop yield grown in rotation, followed by treatment T6 (100% RDN through potato peel compost (PPC) based formulation) and T2 (100% RDN through FYM). The increase in yield was 75.0, 44.3 and 33.1% during first year and 72.6, 45.9 and 31.0% during second year, respectively, over control. Treatment T4 also significantly enhanced system uptake of N, P and K as well as system gross returns and net returns, resulting in 65.6, 84.9, 69.5, 50.7 and 55.2% higher returns during first year and 68.6, 80.5, 73.9, 50.0 and 54.2% higher returns during second year, respectively, over control. Furthermore, treatment T4 significantly improved agronomic nitrogen use efficiency and apparent recovery by 151.6 and 2.0% in baby corn, 74.2 and 1.5% in kabuli gram, 55.7 and 13.9% in veg cowpea over T7, respectively, averaged across two years of study. Based on these results, it is recommended to adopt (T4) 100% RDN through PHA based formulation, and (T6) 100% RDN through PPC based formulation in the area with a shortage of FYM but with the availability of rice husk ash or pototo peels for sustainable utilization of the agricultural wastes and improving the agricultural sustainability.